Formulasi ekstrak fraksi etanol kulit biji kakao (Theobroma cacao L.) sebagai antioksidan alami pada sabun padat - Selly Harnesa Putri; Resha Nurvabilla; Asri Widyasanti (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
A cocoa bean shell is a waste from cocoa bean processing that contains active compounds such as flavonoids, polyphenols, saponins, and tannins, where these compounds are antioxidant compounds that can be utilized as natural antioxidants in soap. This study aimed to determine the formulation by adding cocoa bean shell extract that produces solid soap with the highest antioxidant activity according to SNI 3532:2021. The Complete Randomized Design (CRD) method was used in this study with concentration treatments, which were F0 = 0% (w/v), F1 = 1% (w/v), F2 = 2% (w/v), F3 = 3% (w/v), F4 = 4% (w/v), F5 = 5% (w/v), and F6 = 6% (w/v), on moisture content, acidity (pH), organoleptic, irritation, and antioxidant activity of solid soap. The results showed that cocoa bean shell extract had an IC50 value of 68.12 ppm. The moisture content value of solid soap was in the range of 14.21-23.11%, pH 8.88-9.05, antioxidant activity of 43.33-61.46%, and non-irritating. Thus, the solid soap formulation with the highest antioxidant activity and according to SNI 3532:2021 was solid soap with the addition of 5% extract (F5).